PEMBELAJARAN BAHASA INGGRIS UNTUK SISWA SEKOLAH DASAR DALAM PERSPEKTIF FUN AND ACTIVE LEARNING APPROACH : SEBUAH REFLEKSI TEORETIS - RENATO GEMA NUGRAHA HUTABARAT (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This paper is a theoretical reflection on learning English in terms of a fun and active learning approach. English becomes one of the important soft skills mastered because it will become a necessity in global society. The global association for various interests will fail to achieve the main goals set just because of the longevity of the language. This article is a literature review, with data sources being the results of studies (both empirical / experimental and theoretical) to be analyzed by reflection analysis. Reflection analysis will find highlights from reality that can sharpen our understanding of the learning approach. The main theory used is the Critical Period Hypothesis of Lennerberg. Furthermore, this paper is more descriptive qualitative.The results of the study show that the reality of learning English for elementary school children must pay attention to brain elasticity that is influenced by the approach used. The joy zone gives an opening to the memory bar and the game with a variety of variations provides unlimited stimulation of creativity.